EVALUACIÓN DEL POTENCIAL INTERPRETATIVO PARA EL APROVECHAMIENTO TURÍSTICO DE LOS SITIOS DESTINADOS A LA PESCA VIVENCIAL DE LAS ÁREAS PROTEGIDAS DE GALÁPAGOS - Patricio Lozano Rodríguez; Keyla Castro (European Scientific Journal, ESJ, 2015)
The promotion of the conservation of natural areas has become a global priority. This is because it safeguards the heritage of the planet which in turn generates the ecosystem services which affects human welfare. An edge of this challenge is the awakening of visitors to the natural and cultural values of the aforementioned areas, with the aim of assessing the heritage and contributing to its conservation. This is why heritage interpretation is defined as a tool for the management of visitors in protected natural areas, because it also develops criteria for conditioning visiting sites that meets public purposes of sustainable use and tourism. However, this context has led the Directorate of the Galapagos National Park to consider the statements in the Special Regulations for Tourism in Protected Natural Areas. This is with the aim of boosting alternatives for people who are currently conducting small-scale fishing, to switch to a form of tourism called experiential fishing. Hence, the park has 37 authorized fishing operations experiential tourism development of 19 resting places. To operationalize this initiative and encourage a visitor’s management strategy according to the management of protected areas of Galapagos, it is necessary to measure as accurately as possible the features and performing conditions that have these resting places. This process is characterized by applying a method to decrease subjectivity and measure the interpretive potential of each site visit in the study area. This process consists of four components: a) characterization of the study area, b) inventory interpretative resources, c) index interpretive potential, and d) coverage interpretive potential. These components shows that the 19 resting places for the tourist operation in the form of experiential fishing in protected areas of Galapagos which are concentrated in seven centers in the arid coastal vegetation, have a high degree of naturalness. They denote their relevant physical characteristics such as rocky or low rocky platforms, mangrove areas, beaches, lava cones, and intertidal landscape. Thus, this is all associated with the flora and fauna of the archipelago emblematic. Also, its active and ongoing management and interpretive condition is high. All these traits conclude that 68% of the resting places of protected areas of Galapagos have a Very High (IPI - MA) interpretive potential, while 32% have a High (IPI - A) interpretive potential. The resting place intended for tourist operations in the form of experiential fishing presents a Potential Interpretive Index (IPI) of 0.82, which is too high (IPI - MA). In other words, it has resources with exceptional features to be interpreted. In addition, it boosts visitor’s management strategy from the core three and six which are the sites that concentrate on a break (IPI- MA).